Pemanfaatan Teknologi Informasi dalam Pelaksanaan E-Government di Desa Sipodeceng - Ashar, Ashar; Irwan, Irwan; Herman Dema (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study discusses the utilization of information technology in supporting the implementation of e-government in Sipodeceng Village, Baranti District, Sidenreng Rappang Regency. E-government is a public service digitalization initiative aimed at improving efficiency, transparency, and accountability in government administration. The objective of this research is to explore how information technology is applied to support government services and to analyze the factors that influence its utilization. This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Informants in this study include the village secretary, the web management staff, and members of the community who use digital village services. The data were analyzed using NVivo 12 software to identify dominant themes. The findings show that information technology, through the SIBERAS application, has had a positive impact on administrative service processes, particularly in terms of speed, efficiency, and data recording. However, several obstacles remain, such as low digital literacy among residents, limited internet infrastructure, and some community members’ preference for traditional, face-to-face services. The factors influencing technology utilization include social factors, affective responses, system complexity, task suitability, long-term consequences, and the availability of supporting facilities. This study recommends enhancing digital literacy training and optimizing technological infrastructure as strategic steps to support the sustainability of e-government at the village level.